Thermal properties of epoxy composites filled with boric acid; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Putkhenpurakalchira M. V. Maniyan Visakkh; Nazarenko O. B. Olga Bronislavovna; Amelkovich Yu. A. Yuliya Alexandrovna; Melnikova T. V. (2015, 2015)
Title screen